Fostering Cultural Citizenship: The Implementation of Traditional Dress Regulation at Yapenthom 1 Junior High School - Evarista, Maria; Mayaputri, Velmi; Nasa, Rikardus (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
Indonesia's local cultural heritage faces significant challenges amidst the accelerating forces of globalization, which increasingly undermine traditional values, particularly among younger generations vulnerable to foreign cultural influences. In an effort to safeguard this heritage, the Indonesian government has introduced policies mandating the use of traditional attire within educational institutions as a strategy for cultural preservation. This study investigates the implementation of such a regulation at Yapenthom 1 Junior High School, focusing on students’ perceptions and its broader impact on the school’s cultural environment. Employing a qualitative research design, data were gathered through Focus Group Discussions (FGDs) with students, as well as in-depth interviews with teachers and school leadership. The findings indicate that students generally perceive the traditional dress policy as an effort to maintain cultural identity and promote respect for cultural diversity. However, a segment of students expressed concerns over the policy’s perceived constraints on personal expression. The regulation is seen to positively influence character education by instilling values of discipline and responsibility, while also enhancing the effectiveness of the BelaSikka program. This study offers valuable empirical insights for policymakers seeking to design culturally responsive educational strategies that balance heritage preservation with the evolving needs of a diverse student population.